Control of Hot Carrier Relaxation in CsPbBr3 Nanocrystals Using Damping Ligands. (15th February 2022) - Zeng, Peng; Ren, Xinjian; Wei, Linfeng; Zhao, Haifeng; Liu, Xiaochun; Zhang, Xinyang; Xu, Yanmin; Yan, Lihe; Boldt, Klaus; Smith, Trevor A.; Liu, Mingzhen
Abstract: In photon‐conversion processes, rapid cooling of photo‐induced hot carriers is a dominant energy loss channel. We herein report a 3‐fold reduced hot carrier cooling rate in CsPbBr3 nanocrystals capped with a cross‐linked polysiloxane shell in comparison to single alkyl‐chain oleylamine ligands. Relaxation of hot charge carriers depends on the carrier‐phonon coupling (CPC) process as an important channel to dissipate energies in nanostructured perovskite materials. The CPC strengths in the two samples were measured through cryogenic photoluminescence spectroscopic measurements. The effect of organic ligands on the CPC in CsPbBr3 nanocrystals is elucidated based on a damped oscillation model. This supplements the conventional polaron‐based CPC model, by involving a damping effect on the CPC from the resistance of the ligands against nanocrystal lattice vibrations. The model also accounts for the observed linear temperature‐dependence of the CPC strength. Our work enables predictions about the effect of the ligands on the performance of perovskite nanocrystals in future applications. Abstract : A model for the damping of the carrier‐phonon coupling in all‐inorganic perovskite nanocrystals (PeNCs) was proposed by considering the mechanical resistance of the ligands. Correspondingly the hot carrier cooling process was slowed down by 3‐fold in CsPbBr3 PeNCs by tuning the rigidity of the layer of organic capping ligands.